Interfejsy intymności. Tendencje intymistyczne we współczesnych grach wideo - Kubiński, Piotr (Załącznik Kulturoznawczy, 2021)
The article concentrates on a specific tendency that can be observed in some video games created in recent years. This trend is that more and more video games present an intimate perspective and focus on the individual experience of the protagonist. The author of the article approaches the phenomenon in question mainly from the interpretative and genological perspective, since video games are not a media form commonly identified with the expression of intimate, formative or identitycreating experiences. The author starts with an analysis of the reasons why video games and intimistic texts are commonly perceived as very distant genre forms. Then he analyzes those video games that represent the intimistic tendency: Bury me, my Love (The Pixel Hunt, 2017), A Normal Lost Phone (Accidental Queens, 2017) and Wanderlust: Travel Stories (Different Tales, 2019). The analysis leads to the following conclusions: what is common for all the three discussed games is i.a. a particularly important role of the text as the basic semiotic material in which the game is realized. Even though this concentration on the word is not a necessary condition of intimistic poetics – it definitely helps introducing such a dimension into the work. What is more, two of the three discussed games use the strategy of remediating a smartphone. In both cases, the creators designed new interfaces modeled on the real ones and turned navigating on the phone screen into basic game mechanics. This, in turns, means that intimistic tendencies in video games stimulate reaching for new genre forms. This process of remediation is possible mainly because modern intimacy has shifted very clearly towards the digital, and smartphones have become its basic tool. This phenomenon, which the author of the article calls ‘intimacy 2.0’, is a result of the fact that: (a) contemporary culture is deeply anchored in the digital and its interfaces, and (b) the importance of smartphones in everyday communication and media consumption has been growing enormously in recent years. The final conclusion of the paper is as follows: all the discussed games use an intimate perspective to evoke empathy, which was not a typical video game design goal. This is especially interesting, given the fact, that all the analyzed games remain primarily commercial products that are driven by the laws of the market.